Clinico-Histopathological Analysis of Colorectal Adenocarcinoma Cases in a Tertiary Hospital of Bangladesh (IAHS Medical Journal, 2026)
Background: Colorectal Carcinoma (CRC) demonstrates geographic variations in presentation. Recent data on clinico-pathological characteristics from Bangladesh remains limited. This study aimed to describe the demographic, risk factors and histopathological profile of colorectal adenocarcinoma patients at a tertiary hospital in Bangladesh.Materials and methods: A cross-sectional observational study was conducted in the Department of Pathology, Chittagong Medical College, Bangladesh, from March 2021 to December 2022. Purposive sampling included 49 surgically resected, histopathologically confirmed primary colorectal adenocarcinoma specimens. Data on demographics, risk factors (Smoking, alcohol, family history) and tumor characteristics (Size, site, morphology) were collected through patient interviews using a structured case record form. Histopathological examination (H&E staining) determined subtype, grade, T stage (Tumour stage) and N stage (Involvement of lymph node).Results: The mean age was 46.63 ± 13.4 years, with 79.6% of patients